Perlindungan Hukum Bagi Penyewa Lahan Di Kawasan Ex PT Gili Trawangan Indah (GTI) - Ananta, Dea Melinda; Wahyuddin, Wahyuddin (Private Law, 2024)
This research aims to determine legal protection for land renters in the Ex PT Gili Trawangan Indah (GTI) area. Furthermore, it determines the pattern of control by the community on the land of Ex PT Gili Trawangan Indah (GTI). The research method used in this research is an empirical legal research method. The research results determine that legal protection given only to tenants of Ex PT Gili Trawangan Indah (GTI) land who have good intentions, parties who do not have good intentions are not appropriate and have legal reasons to obtain legal protection, because the rental agreement executed without honesty, and there is no good faith on the part of the lessor or the lessee and the agreement cause legal consequences in the form of the cancellation of the rental agreement. The land control pattern by the community on the Ex PT Gili Trawangan Indah land is individual control, not in a communal form.